Spatial variation in a top marine predator's diet at two regionally distinct sites. - Martha Gosch; Michelle Cronin; Emer Rogan; William Hunt; Cian Luck; Mark Jessopp (PLoS ONE, 2019)
In ecological studies it is often assumed that predator foraging strategies and resource use are geographically and seasonally homogeneous, resulting in relatively static trophic relationships. However, certain centrally placed foragers (e.g. seals) often have terrestrial sites for breeding, resting, and moulting that are geographically distinct, and associated with different habitat types. Therefore, accurate estimations of predator diet at relevant spatial and temporal scales are key to understanding energetic requirements, predator-prey interactions and ecosystem structure. We investigate geographic variation in the diet of grey seals (Halichoerus grypus), a relatively abundant and widely distributed central place forager, to provide insights into geographic variation in resource use. Prey composition was identified using scat samples collected over concurrent timescales and a multivariate approach was used to analyse diet from two contrasting habitats. Regional differences in prey assemblages occurred within all years (2011-2013) and all seasons (ANOSIM, all p<0.05), apart from in winter. Telemetry data were used to identify core foraging areas and habitats most likely associated with scat samples collected at the two haul-out sites. Regional differences in the diet appear to reflect regional differences in the physical habitat features, with seals foraging in deeper waters over sandy substrates showing a higher prevalence of pelagic and bentho-pelagic prey species such as blue whiting and sandeels. Conversely, seals foraging in comparatively shallow waters had a greater contribution of demersal and groundfish species such as cephalopods and flatfish in their diet. We suggest that shallower waters enable seals to spend more time foraging along the benthos while remaining within aerobic dive limits, resulting in more benthic species in the diet. In contrast, the diet of seals hauled-out in areas adjacent to deeper waters indicates that either seals engage in a more pelagic foraging strategy, or that seals can spend less time at the benthos, resulting in comparatively more pelagic prey recovered in the diet. The substantial differences in prey assemblages over a small spatial scale (<300 km) demonstrates the importance of using regionally-specific diet information in ecosystem-based models to better account for different trophic interactions.